Pain and Cellular Migration Induced by Bothrops jararaca Venom in Mice Selected for an Acute Inflammatory Response: Involvement of Mast Cells - Kondo, Fernanda V.; Cabrera, Wafa H. K.; Ribeiro, Orlando G.; De Franco, Marcelo; Jensen, José Ricardo; Picolo, Gisele; Sant’Anna, Morena B.; Spadafora-Ferreira, Monica; Borrego, Andrea; Ibañez, Olga M.; Starobinas, Nancy (Frontiers in Immunology, 2022)
Bothrops jararaca venom (BjV) can induce mast cells degranulation. In order to investigate the role of mast cells and the interference of the host genetic background in inflammation induced by BjV, we have used mouse strains selected for maximal (AIRmax) or minimal (AIRmin) acute inflammatory response (AIR). Mice were pretreated with and inhibitor of mast cell degranulation, cromolyn (CROM) and injected in footpads or ip with BjV. Pain was measured with von Frey hairs, cell migration in the peritoneum by flow cytometry and reactive oxygen production by chemiluminescence assays. The nociceptive response to BjV was higher in AIRmax than AIRmin mice; however, this difference was abolished by the pretreatment with CROM; BjV induced peritoneal neutrophil (CD11b+ GR-1+) infiltration and ROS secretion in AIRmax mice only, which were partially inhibited by CROM. Our findings evidence a role for mast cells in pain, neutrophil migration and ROS production triggered by BjV in AIRmax mice, who are more susceptible to the action of BjV.